Detección de Malpighamoeba mellificae (Protista: Amoebozoa) en Apis mellifera (Hymenoptera: Apidae) de Argentina - Plischuk, Santiago (2010)
Due to its role as a pollinator and honey producer, the honey bee Apis mellifera L. is considered a beneficial insect. Although Argentina plays a leading role in honey production, there is a considerable gap in knowledge regarding protistan diseases that affect honey bees in the country. The amoeba Malpighamoeba mellificae Prell is an entomopathogenic protist that invades the Malpighian tubules of honey bees and interferes with the excretory process, debilitating the host and possibly facilitating the action of other pathogens. In this contribution, we present the first reports of M. mellificae in Argentina, and provide some initial data about its frecuency, infection intensity, and co-occurrence with Nosema sp. Malpighamoeba mellificae was found in two out of 36 localities surveyed: San Cayetano, in southern Buenos Aires province, and San Carlos de Bariloche, in western Río Negro province.